Augmented Reality and Intraoperative Navigation in Sinonasal Malignancies: A Preclinical Study - Sahovaler, Axel; Chan, Harley H. L.; Gualtieri, Tommaso; Daly, Michael; Ferrari, Marco; Vannelli, Claire; Eu, Donovan; Manojlovic-Kolarski, Mirko; Orzell, Susannah; Taboni, Stefano; de Almeida, John R.; Goldstein, David P.; et al. (Frontiers in Oncology, 2021)
Objective: To report the first use of a novel Augmented Reality (AR) system in open sinonasal tumor resections in preclinical models, and to compare the AR approach with an advanced Intraoperative Navigation (IN) system. Methods: Four tumor models were created. Five head and neck surgeons participated in the study performing virtual osteotomies. Unguided, AR, IN, and AR + IN simulations were performed. Statistical comparisons between approaches were obtained. Intratumoral cut rates was the main outcome. The groups were also compared in terms of percentage of intratumoral, close, adequate, and excessive distances from the tumor. Information of a wearable gaze-tracker headset and NASA-Task-Load-Index questionnaire results were analyzed as well. Results: A total of 335 cuts were simulated. Intratumoral cuts were observed in 20.7%, 9.4%, 1.2% and 0% of the unguided, AR, IN and AR + IN simulations respectively (p<0.0001). The AR was superior than the unguided approach in univariate and multivariate models. The percentage of time looking at the screen during the procedures was 55.5% for the unguided approaches and 0%, 78.5% and 61.8% in AR, IN and AR + IN, respectively (p<0.001). The combined approach significantly reduced the screen-time compared with the IN procedures alone. Conclusion: We reported the use of a novel AR system for oncological resections in open sinonasal approaches, with improved margin delineation compared with unguided techniques. AR improved the gaze-toggling drawback of IN. Further refinements of the AR system are needed before translating our experience to clinical practice.